Purity and the forming of religious traditions in the ancient Mediterranean world and ancient Judaism - Frevel, Christian, 1962-; Nihan, Christophe, 1972- (Dynamics in the History of Religions, 2013)
Purity is a cultural construct that had a central role in the forming and the development of religious traditions in the ancient Mediterranean. This volume analyzes concepts, practices and images associated with purity in the main cultures of Antiquity, and discusses from a comparative perspective their parallel developments and transformations. The perspective adopted is both synchronic and diachronic; the comparative approach takes into account points of contact and mutual influences, but also includes major transcultural trends. A number of renowned specialists contribute a large variety of perspectives and approaches, combining archaeology, epigraphy and social history; in addition, particular attention is given to concepts of purity in ancient Israel and early Judaism as a 'test-case' of sorts. Through its extensive coverage, the volume contributes decisively to the present discussion about the forming of religious traditions in the ancient Mediterranean world.